1991
DOI: 10.1128/iai.59.11.4110-4116.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of spontaneously occurring cytolysin-negative mutants of Actinobacillus pleuropneumoniae serotype 7

Abstract: Actinobacillus pleuropneumoniae serotype 7 strains are shown to spontaneously lose cytolytic activity, with a frequency of approximately 10-4. The phenotypic change is associated with the loss of approximately 8.5 kbp of chromosomal DNA. A genomic fragment encoding the cytolysin and its flanking sequences was cloned and characterized. Also, the corresponding truncated fragment was cloned from a spontaneous mutant. Comparison of the two clones allowed the definition of the excision site. The ends of the excised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 37 publications
(50 reference statements)
1
28
0
Order By: Relevance
“…Escherichia coli strains were cultured in Luria^Bertani (LB) medium supplemented with the appropriate antibiotics (ampicillin, 100 Wg ml 31 ; kanamycin, 50 Wg ml 31 ); for cultivation of E. coli L2155 (vdapA), diaminopimelic acid (1 mM; Sigma Chemical Co., Deisenhofen, Germany) was added. A. pleuropneumoniae strains were cultured in PPLO medium (Difco, Augsburg, Germany) supplemented with NAD (10 Wg ml 31 ; E. Merck, Darmstadt, Germany), L-glutamine (100 Wg ml 31 ; Serva, Heidelberg, Germany), L-cysteine hydrochloride (260 Wg ml 31 ; Sigma), L-cystine dihydrochloride (10 Wg ml 31 ; Sigma), dextrose (1 mg ml 31 ), and Tween 0 80 (0.1%). For the selection of A. pleuropneumoniae transconjugants, chloramphenicol (5 Wg ml 31 ) was added.…”
Section: Media and Growth Conditionsmentioning
confidence: 99%
“…Escherichia coli strains were cultured in Luria^Bertani (LB) medium supplemented with the appropriate antibiotics (ampicillin, 100 Wg ml 31 ; kanamycin, 50 Wg ml 31 ); for cultivation of E. coli L2155 (vdapA), diaminopimelic acid (1 mM; Sigma Chemical Co., Deisenhofen, Germany) was added. A. pleuropneumoniae strains were cultured in PPLO medium (Difco, Augsburg, Germany) supplemented with NAD (10 Wg ml 31 ; E. Merck, Darmstadt, Germany), L-glutamine (100 Wg ml 31 ; Serva, Heidelberg, Germany), L-cysteine hydrochloride (260 Wg ml 31 ; Sigma), L-cystine dihydrochloride (10 Wg ml 31 ; Sigma), dextrose (1 mg ml 31 ), and Tween 0 80 (0.1%). For the selection of A. pleuropneumoniae transconjugants, chloramphenicol (5 Wg ml 31 ) was added.…”
Section: Media and Growth Conditionsmentioning
confidence: 99%
“…Although multiple factors are believed to be involved in the virulence of A. pleuropneumoniae infection and the exact mechanism of infection is not yet completely understood, previous studies indicated that Apx toxins correlate strongly with the virulence of the bacterium (Tascon et al, 1994;Frey, 1995;Reimer et al, 1995). The Apx toxins are thought to be of particular importance among the virulence factors because the toxins can induce protective immune responses against the bacterial infection, as demonstrated previously using several mutants (Anderson et al, 1991;Tascon et al, 1994;Reimer et al, 1995;Prideaux et al, 1999;Fuller et al, 2000).…”
Section: Introductionmentioning
confidence: 75%
“…Previously we had administered the toxin-deficient strain HS93 Tox Ϫ to pigs at doses similar to that of the challenge used in this experiment and autopsied the pigs at day 5 but observed no lesions. Apxdeficient mutants of APP produced by either chemical or transposon mutagenesis have previously been shown to have a reduced ability to induce lung lesions (1,15,17,29,30,33,34). The six unvaccinated pigs challenged with HS25 showed numerous lung lesions that were visible on autopsy, indicating that the level of challenge used was sufficient to induce lesions in unprotected animals.…”
Section: Discussionmentioning
confidence: 95%
“…These secreted toxins, or Apx toxins, are members of the RTX toxin family (11)(12)(13). The role of Apx toxins in A. pleuropneumoniae virulence was first demonstrated with spontaneous and chemically induced nonhemolytic mutants which were found to be completely or partially avirulent; this role was later confirmed by using transposon mutagenesis (1,15,17,29,30,33,34). At least three different Apx toxins are produced by A. pleuropneumoniae, designated ApxI, ApxII, and ApxIII.…”
mentioning
confidence: 98%